PENGARUH PROFESIONALISME AUDITOR DAN ETIKA PROFESI TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS PADA KANTOR AKUNTAN PUBLIK DI WILAYAH PALEMBANG - Dwi Septa Aryani; Shinta Dwi Anggraeni (JURNAL KOMPETITIF, 2018)
In performing its duties an auditor is required to work professionally and honestly by complying with anyshape of applicable ethics especially when considering the materiality level of a financial statement. Auditor is having a high professionalism attitude, therefore understanding and applying the applicable professional ethics is a must for every auditor. This research essentially discusses how much relationship between professionalism and professional ethics effected the level of materilitas.Result of  the research are: First, simultaneously Professionalism significantly influence the dependent variable level of materiality in examination of clients financial statements. Secondly, all variables (Professionalism and Professional Ethics) significantly influence the consideration of materiality level in the examination of a financial report. From the results of the research, the researcher gives advice for the auditor to keep improving their attitude of professionalism and more understanding the professional ethics that has been established for auditor so that auditor could considering the materiality level of financial report appropriately. Keywords: Auditors Professionalism, Professional Ethics and Materiality Level